Colmeia design estratégico: ferramenta orientada às abordagens críticas de design para repensar a sustentabilidade na moda - Müller, Victoria Dani (Universidade do Vale do Rio dos Sinos, 2023)
This research presents a qualitative and exploratory character on critical design approaches for sustainability in the fashion industry. The research problem is as follows: How can critical design approaches, combined with strategic design, assist fashion designers in critically reflecting on their projects and the impacts caused by the industry, seeking disruptive approaches towards sustainability? The objective was to develop a strategic design tool that considers critical design approaches in fashion design processes aiming to integrate sustainable production and consumption modes in fashion. The method used firstly involved bibliographic research to problematize the research context and study speculative critical approaches, collection development processes in fashion, sustainable approaches, and strategic design. Based on the initial research, a tool called the "Colmeia Strategic Design" was developed, based on the concept of prompt cards. It consists of a set of hexagonal cards aimed at encouraging speculation and critical thinking regarding fashion while assisting in the development of sustainable solutions for the fashion industry. The tool was first tested in a pilot and then in a workshop. After the pilot, some changes were made to the tool, including the addition of cards presenting sustainability principles, adding text to image-only cards, and developing preparatory materials such as a video on the current fashion industry context and a presentation on how the tool works. The workshop tool contained 46 cards distributed into 6 categories: speculative cards, purpose, wildcard, experimentation and prototyping, critical approaches, and product/service definition. Through the workshop, it was observed how the developed tool aided discussions, enabling moments of design openness and encouraging reflection on various issues in the fashion world. After the workshop, further changes were made to the tool, this time dividing the cards into three levels: see, predict, and make see, and into five categories: speculation; purpose; tools and approaches; actors and feedback. Additionally, new cards were added, such as cards presenting concepts of different economies, and wildcard cards were distributed across all categories. The feedback category was added to guide participants throughout the dynamics, making the moment more intuitive and reminding them to use all the cards. These changes were made to transform the tool into a gamified system, incorporating elements from games to make the dynamics more intuitive and engaging for participants. Finally, the tool proved capable of providing moments of design openness in fashion, aiming to observe new problems and sustainable solutions through critical thinking and speculation.
Keywords: Design; Sustentabilidade; Moda; Sustainability; Fashion; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial